Case Study of Mobile Legends Online Game Players in Late Childhood - Alwiah, Nurul; Daud, Muh. (Polteknik Ilmu Pemasyarakatan, 2023)
Mobile legends online game players from late childhood who are accustomed to receiving and uttering hate speech can impact moral development. This research aims to determine the description of hate speech and the moral development of children who become mobile legends online game players who express hate speech in late childhood. The method used in this research is a qualitative research method with a case study approach. The sampling technique used was the purposive sampling technique. The respondents in this study were two people in late childhood and four informants who were significant others. The results of the research show that the picture of hate speech obtained takes the form of dysphemism, labeling, and stereotypes. The hate speech uttered takes the form of euphemisms, dysphemisms and labeling. The moral development of mobile legends online game players from late childhood is different for each respondent. The conclusion in this research is that Respondent 1 is still adjusting to reach stage II of moral development and Respondent 2 is at stage III of moral development.